CARBON PASTE ELECTRODE MODIFIED BY MOLECULARLY IMPRINTED POLY(3-AMINOPHENOL) FOR SIMULTANEOUS VOLTAMMETRIC DETERMINATION OF IBUPROFEN AND PARACETAMOL - Hasanah Pratiwi, Nur
Ibuprofen is known as an antipyretic, anti-inflammatory, and analgesic drug that is usually used to relieve muscle and tooth pain, rheumatic arthritis, fever, and migraines. Paracetamol or acetaminophen is also an antipyretic and analgesic drug that is usually found in fever and flu medications. These two compounds are present in a mixture in the pharmacology industry, so it is necessary to develop an accurate and simultaneous analytical method. In this research, a voltammetric method developed using carbon paste electrode (EPK) modified with molecularly imprinted poly(3-aminophenol) to analyze ibuprofen and paracetamol simultaneously, sensitively, and accurately. EPK modification was carried out by electropolymerization technique on the electrode surface. The optimization and method validation stages were conducted to obtain good measurement performance. In the optimization stage of electropolymerization of MIP poly (3- aminophenol) the optimum composition was obtained 1:3 (ibuprofen: 3- aminophenol) with a total of 15 cycles of electropolymerization. Ibuprofen solution can be measured well at pH 5 in a mixture of 0.1 M phosphate and acetate buffer solution. The resulting EPK-MIP can increase the sensitivity of ibuprofen and paracetamol measurements performed simultaneously. EPK-MIP also has a fairly good repeatability of ibuprofen measurement with an RSD value of 7.114%.